ANALYSIS OF THE WORK CARRIED OUT ON TAX ADMINISTRATION OF LARGE TAXPAYERS IN UZBEKISTAN IN 2024 (International Conference on Educational Discoveries and Humanities, 2025)
This article analyzes foreign experience in implementing tax administration of large taxpayers, and as a result of these analyzes, issues of improving the tax legislation of the Republic of Uzbekistan, proposals and recommendations for further improving tax administration of large taxpayers were developed.